Hyperacute Intracerebral Hemorrhage Complicating Carotid Stenting Should Be Distinguished from Hyperperfusion Syndrome - Buhk, J.-H.; Cepek, L.; Knauth, M. (American Journal of Neuroradiology, 2006)
SUMMARY: We describe a patient who experienced a fatal ipsilateral basal ganglia hemorrhage within an hour after carotid angioplasty and stent placement. In the few similar cases published there were no prodromata, but hyperacute onset of severe neurologic deterioration corresponding to intracerebral hemorrhage (ICH). Our findings suggest that besides the delayed ICH that is associated with hyperperfusion syndrome (HPS), a second type of hyperacute and usually fatal ICH exists that resembles hypertensive hemorrhage.